The Characteristics of the Traditional Chinese Theather Jing Ju - Tri Utari Ismayuni; Nanda Saputra (Lakhomi Journal Scientific Journal of Culture, 2021)
The title of the paper is “Characters in Jing Ju Traditional Chinese Theatre”. In This paper, the writer wants to analyze the characters from Jing Ju Traditional theatre. This paper talks about the method of the analysis which is used by the writer is descriptive comparative method. And the theory which is used in comparing and analyzed the characters and the meanings of the analysis, the writer show and describes the character which exists in Jing Ju theatre, the meaning of the mask colors from each theatre.